THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (E-WOM) AND BRAND TRUST ON ONLINE PURCHASE DECISIONS OF SKINCARE PRODUCTS IN LAZADA - Jenifer Mamoto; Emilia M. Gunawan (Universitas Sam Ratulangi, 2023)
This study aims to know the influence of electronic word of mouth (E-WOM) and brand trust on online purchase decision of skincare products in Lazada. The research sample is 100 respondents. The data collected by questionnaire and distributed online. The sampling method used in this study is a purposive sampling. The data analysis method in this study is multiple linear regression and using SPSS as a data processing tool. The result shows that electronic word of mouth partially has a positive and significant influence on online purchase decisision. Brand trust partially has a positive and significant influence on online purchase decision. Electronic word of mouth and brand trust simultaneously have a positif and significant influence on online purchase decision. Keyword: electronic word of mouth, brand trust and online purchase decision